2015
DOI: 10.1002/cncr.29204
|View full text |Cite
|
Sign up to set email alerts
|

Automated pain intervention for underserved minority women with breast cancer

Abstract: BACKGROUND Minority patients with breast cancer are at risk for undertreatment of cancer-related pain. We evaluated the feasibility and efficacy of an automated pain intervention for improving pain and symptom management of underserved African American and Latina women with breast cancer. METHODS Sixty low-income African American and Latina women with breast cancer and cancer-related pain were enrolled in a pilot study of an automated, telephone-based interactive voice response (IVR) intervention. The interv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
79
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(81 citation statements)
references
References 32 publications
1
79
0
1
Order By: Relevance
“…In total, 3412 titles were identified by searching four databases and by screening reference lists. No new studies were identified in the updated MEDLINE search (December 2015); however, one new article was identified after the initial database searches17 which was linked to the research team of an earlier study 18…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…In total, 3412 titles were identified by searching four databases and by screening reference lists. No new studies were identified in the updated MEDLINE search (December 2015); however, one new article was identified after the initial database searches17 which was linked to the research team of an earlier study 18…”
Section: Resultsmentioning
confidence: 99%
“…Nine trials used pen and paper,19 23 25 26 28 34 40 45 four used touch screen devices or personal digital assistants to collect the data,20 36 37 41 three used automated telephone monitoring,17 18 35 one used web-based systems,21 and in two trials, the patient was interviewed by a nurse27 or a health educator29 for the data. One study offered a choice between automated telephone monitoring or online monitoring 33…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations